2004
DOI: 10.1590/s0100-69912004000200004
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação da reinfecção peritoneal após peritonite fecal em ratos

Abstract: OBJETIVO: Há poucos estudos sobre os efeitos de uma nova infecção após peritonite séptica. Com o objetivo de compreender melhor esta situação, realizou-se o presente experimento tendo como parâmetro o papel do tempo neste fenômeno. MÉTODO: Foram utilizadas 36 ratas Wistar adultas, submetidas a peritonite fecal com injeção intraperitoneal de uma solução de fezes de ratos. Os animais foram divididos em quatro grupos (n = 9): Grupo 1A - controle: injeção intraperitoneal de solução de fezes com uma quantidade sabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 16 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…Peritonitis induction in rats was carried out 70 days after the surgical procedures by administering the suspension prepared with 2g of fresh feces (of the animals themselves) at the dose 10 mL/Kg weight – this dose is known to be lethal 18 . This suspension was prepared by diluting feces in 17 mL of sodium chloride solution at 0.9% and filtering it in gauze to allow its passage through the needle.…”
Section: Methodsmentioning
confidence: 99%
“…Peritonitis induction in rats was carried out 70 days after the surgical procedures by administering the suspension prepared with 2g of fresh feces (of the animals themselves) at the dose 10 mL/Kg weight – this dose is known to be lethal 18 . This suspension was prepared by diluting feces in 17 mL of sodium chloride solution at 0.9% and filtering it in gauze to allow its passage through the needle.…”
Section: Methodsmentioning
confidence: 99%
“…The microbiota also interfered in both the gastrojejunoduodenal and gastrocoloduodenal interposition. 22 The observation of the groups at the end of each weekly interval revealed different health status' among the 40 subjects. The determining factor for the improvement of dogs was the jejunal interposition, which stabilized the losses before the end of the postoperative period.…”
Section: Surgical Complicationsmentioning
confidence: 96%
“…22 The volume of postoperative intestinal excretion for 120 days was sometimes small in the beginning and increased later. It was found that, with the gastroduodenal interposition of jejunum and colon segments, diarrhea discharges affected the totality of dogs.…”
Section: Clinical Evaluationmentioning
confidence: 99%
See 1 more Smart Citation